Economic Activity and Greenhouse Gas Emissions: An Empirical Study of the Indonesian Manufacturing Industry - Fawzia, Annisa Ayu; Fawzia, Aulia Valerie; Nurjani, Emilya; Ahmada, Benarifo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Manufacturing industry plays significant role in the Indonesian economy. However, this sector was the largest contributor to greenhouse gas (GHG) emissions in 2022, reaching 38% of total emissions released by all sectors. The purposes of this study are to identify characteristics and trends of economic activity and GHG emissions from fuel consumption across 24 manufacturing subsectors, and to analyze the effect of some economic variables on GHG emissions of the manufacturing industry in Indonesia. Economic variables from 2012-2022, including machinery maintenance intensity, labor intensity, resource-use intensity, value-added, and GHG intensity, were analyzed using descriptive statistics and fixed-effect model panel regression. The results show that labor intensity in the manufacturing subsector tends to decline, while resource use intensity and value-added are increasing. Meanwhile, machinery maintenance intensity shows considerable variation without consistent concentration in particular subsectors. Panel data regression indicates that maintenance intensity and labor intensity have significant positive effect on GHG intensity, while resource-use intensity and value-added have significant negative effect. Based on these results, interventions on economic variables can influence GHG emission levels. This study recommends fiscal policy interventions, such as subsidies for environmentally friendly equipment and incentives for green industries, to strengthen the performance of environmentally friendly industries.